The potential of virtual tourism in the recovery of tourism industry during the COVID-19 pandemic. Issue 3 (1st February 2022) - Lu, Junyu; Xiao, Xiao; Xu, Zixuan; Wang, Chenqi; Zhang, Meixuan; Zhou, Yang
ABSTRACT : The COVID-19 pandemic has imposed tremendous impacts on the tourism industry worldwide. The tourism sector can take advantage of the new technology (e.g. virtual tourism), to respond to the challenges. This study aims to investigate factors influencing people's acceptability in using virtual tourism during the pandemic in China and explore how virtual tourism can aid the recovery of tourism industry during and after the pandemic. We explore this through a mixed-methods approach. Our results show that the use of virtual tourism can be partially explained by the theory of planned behaviour. Virtual tourism has a strong influence on people's on-site destination choices and can be used as an effective marketing tool to promote destinations and a platform to sell souvenirs and products. Virtual tourism can be an entertainment activity to bring immersed experience to people without being actually in the destinations, and thus reinforce stay-at-home order and help contain COVID-19. Even after the pandemic is over, people still show willingness to use virtual tourism for diverse purposes. The qualitative data also suggest virtual tourism can help promote sustainable tourism by reducing unnecessary greenhouse gas emissions from transportation and enhance 'virtual accessibility' especially for the elderly and disabled with limited mobility.